2005
DOI: 10.1007/s00213-005-2271-x
|View full text |Cite
|
Sign up to set email alerts
|

GABA-benzodiazepine receptor function in alcohol dependence: a combined 11C-flumazenil PET and pharmacodynamic study

Abstract: In summary, our study suggests that alcohol dependence in man is associated with a reduced EEG sleep response to the benzodiazepine agonist, midazolam, which is not explained by reduced BDZ receptor occupancy, and is consistent with reduced sensitivity in this measure of GABA-BDZ receptor function in alcohol dependence. The lack of change in other functional measures may reflect a differential involvement of particular subtypes of the GABA-BDZ receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…Furthermore, the GABA/benzodiazepine receptor availability in the cerebellum and occipital lobe at 1 week of abstinence was correlated with the severity of ethanol withdrawal determined in the subjects every 6 h immediately after admission to the clinic (Staley et al 2005). Using [ 11 C]-flumazenil PET to measure the pharmacokinetics and pharmacodynamics of midazolam, Lingford-Hughes et al (2005) showed that ethanol dependence was associated with decreased midazolam-induced time asleep in the absence of reduced benzodiazepine receptor occupancy in ethanol-dependent patients abstinent for at least 6 weeks. The authors hypothesized that this reduced sensitivity in ethanol dependence may reflect a difference in the subunit profile of the GABA A receptors, either as part of the vulnerability to, or as a consequence of their ethanol dependence.…”
Section: Human Alcoholicsmentioning
confidence: 99%
“…Furthermore, the GABA/benzodiazepine receptor availability in the cerebellum and occipital lobe at 1 week of abstinence was correlated with the severity of ethanol withdrawal determined in the subjects every 6 h immediately after admission to the clinic (Staley et al 2005). Using [ 11 C]-flumazenil PET to measure the pharmacokinetics and pharmacodynamics of midazolam, Lingford-Hughes et al (2005) showed that ethanol dependence was associated with decreased midazolam-induced time asleep in the absence of reduced benzodiazepine receptor occupancy in ethanol-dependent patients abstinent for at least 6 weeks. The authors hypothesized that this reduced sensitivity in ethanol dependence may reflect a difference in the subunit profile of the GABA A receptors, either as part of the vulnerability to, or as a consequence of their ethanol dependence.…”
Section: Human Alcoholicsmentioning
confidence: 99%
“…When a saturation method or V T was used with [ 11 C]flumazenil or [ 123 I]iomazenil, group differences were either absent (Lingford-Hughes et al, 2000; Lingford-Hughes et al, 2005; Litton et al, 1993) or reversed (Jalan et al, 2000). However, recall that this latter study included alcohol-addicted individuals of older age and with liver disease, which may have affected findings.…”
Section: Gabaergic Changes In Drug Addiction (Table 2)mentioning
confidence: 99%
“…For instance, GABA A receptor density can be inferred in PET using [11C]flumazenil, and more recently [18F]AH114726 (Rodnick, et al, 2013), GABA A benzodiazepine receptor antagonists, and [123l]iomazenil, a GABA A benzodiazepine receptor inverse agonist. Using these radiotracer methods, reduced GABA A receptor densities have been reported in 1-month, 3-month and 7-month abstinence alcohol dependent patients, and from brain regions that include the medial prefrontal cortex and cerebellum (Abi-Dargham, et al, 1998; Lingford-Hughes, et al, 2000; Lingford-Hughes, et al, 1998; Lingford-Hughes, et al, 2005). Conversely, elevated GABA A receptor density has been reported earlier during the course of abstinence, at 1-week, which normalized to control levels by 4-weeks (Staley, et al, 2005).…”
Section: Setting the Stagementioning
confidence: 99%